Physics with antihydrogen. (6th October 2015) - Bertsche, W A; Butler, E; Charlton, M; Madsen, N
Abstract: Performing measurements of the properties of antihydrogen, the bound state of an antiproton and a positron, and comparing the results with those for ordinary hydrogen, has long been seen as a route to test some of the fundamental principles of physics. There has been much experimental progress in this direction in recent years, and antihydrogen is now routinely created and trapped and a range of exciting measurements probing the foundations of modern physics are planned or underway. In this contribution we review the techniques developed to facilitate the capture and manipulation of positrons and antiprotons, along with procedures to bring them together to create antihydrogen. Once formed, the antihydrogen has been detected by its destruction via annihilation or field ionization, and aspects of the methodologies involved are summarized. Magnetic minimum neutral atom traps have been employed to allow some of the antihydrogen created to be held for considerable periods. We describe such devices, and their implementation, along with the cusp magnetic trap used to produce the first evidence for a low-energy beam of antihydrogen. The experiments performed to date on antihydrogen are discussed, including the first observation of a resonant quantum transition and the analyses that have yielded a limit on the electrical neutrality of the anti-atom and placed crude bounds on its gravitational behaviour. Our review concludes with an outlook, including the new ELENA extension to the antiproton decelerator facility at CERN, together with summaries of how we envisage the major threads of antihydrogen physics will progress in the coming years.